Bone remodeling, particle disease and individual susceptibility to periprosthetic osteolysis - Gallo, J; Raska, M; Mrázek, F; Petrek, M (Physiological research, 2008)
Bone remodeling is a tightly coupled process consisting of repetitive cycles of bone resorption and formation. Both processes are governed by mechanical signals, which operate in conjunction with local and systemic factors in a discrete anatomic structure designated a basic multicellular unit (BMU). The microenvironment around total joint arthroplasty is a dynamic and complex milieu influenced by the chemical and physical stimuli associated with servicing the prosthesis. A key factor limiting the longevity of the prosthesis is polyethylene wear, which induces particle disease, and this may lead to increased and prolonged activity of BMUs resulting in periprosthetic osteolysis. Several pathways regulating BMU function have been reported in the past, including RANKL/RANK/OPG/TRAF6, TNF-alpha/TNFR/TRAF1, and IL-6/CD126/JAK/STAT. Moreover, the expression and functional activity of all these molecules can be affected by variations in their genes. These may explain the differences in severity of bone defects or prosthetic failure between patients with similar wear rates and the same prosthesis. Simultaneously, this data strongly support the theory of individual susceptibility to prosthetic failure.
Keywords: Prosthesis Failure; osteoklasty; hodnocení rizik; fibroblasty; Risk Assessment; Risk Factors; Fibroblasts; osteoblasty; mechanický stres; signální transdukce; Osteoblasts; Disease Susceptibility; Osteolysis; lymfocyty; Signal Transduction; Stress, Mechanical; artroplastiky kloubů; Bone Remodeling; Arthroplasty, Replacement; lidé; protézy kloubů; Humans; Lymphocytes; remodelace kosti; rizikové faktory; Osteoclasts; Joint Prosthesis; selhání protézy; náchylnost k nemoci; osteolýza